EXPLORING CHILDREN’S PERCEPTIONS OF THE “READ ALONG BY GOOGLE APPLICATION” TO ENHANCE READING MOTIVATION - Dea Syafitri; Repelita Waty Kembaren , Farida (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
This study stems from concerns about declining reading interest among children in the digital era and the need for literacy approaches compatible with technological progress. It aims to explore elementary school children’s perceptions of the Read Along by Google application and analyze its impact on enhancing reading motivation within a home-based learning context. A qualitative approach with a case study design was used, collecting data from ten children aged 9 to 11 through naturalistic observations, semi-structured interviews, and parental reflective journals over two months. The study took place in Tanjung Morawa, North Sumatra, Indonesia—a suburban area where access to digital learning tools is improving but still uneven. Findings indicate that children viewed the app as an enjoyable, non-intimidating reading companion. Features such as real-time voice feedback from Diya, a star-based reward system, and engaging visual stories significantly boosted emotional involvement and reading interest. The children began reading independently, showed increased confidence, and established consistent daily reading habits. Parents observed a shift in behavior—from reading as a duty to reading by choice. These findings support the Self-Determination Theory (Deci & Ryan), Sociocultural Theory (Vygotsky), and the concept of Technology-Enhanced Learning (Laurillard), all of which emphasize fulfilling psychological needs, using appropriate learning tools, and encouraging digital interaction. Read Along demonstrates potential as a transformative tool for nurturing children’s reading interest and habits, especially in informal settings such as the home.